A Psychological Study of Increasing Suicidal Tendency in Present Scenario of COVID-19 Crisis - Soni, Shalini (SCHOOL SCIENCE, 2020)
In this medical emergency of COVID-19, increasing suicidal tendencies all over the world can be considered a mental health emergency. The speed at which suicide cases shoot up is alarming. Now COVID-19 will not be just a medical phenomenon. Day by day, it is adversely affecting people not only physically but also mentally as well as emotionally. Maybe its impact and consequences vary from person to person, but we cannot deny that, due to this outbreak, everybody is feeling stressed and having anxiety. In this situation, when a person is already emotionally unstable negative thoughts can dominate him easily. Mental health can be ensured when we are vigilant about the emotion, thought, and behaviour of others and ourselves. The present study aims to provide a picture of increasing suicidal tendencies among individuals in the present scenario of the COVID-19 crisis.